Phyllanthus spp. induces selective growth inhibition of PC-3 and MeWo human cancer cells through modulation of cell cycle and induction of apoptosis. - Tang, Y.; Jaganath, I.B.; Sekaran, S.D. (Public Library of Science, 2010)
Phyllanthus plant exerts its growth inhibition effect in a selective manner towards cancer cells through the modulation of cell cycle and induction of apoptosis via caspases activation in melanoma and prostate cancer cells. Hence, Phyllanthus may be sourced for the development of a potent apoptosis-inducing anticancer agent.